The Ethanol Extract of the Inner Bark of Caesalpinia pyramidalis (Tul.) Reduces Urinary Bladder Damage during Cyclophosphamide-Induced Cystitis in Rats - Janaína P. Moraes; Denyson S. Pereira; Alexandre S. Matos; Danielle G. Santana; Cliomar A. Santos; Charles S. Estevam; Ricardo Fakhouri; Waldecy de Lucca Junior; Enilton A. Camargo (The Scientific World Journal, 2013)
Hemorrhagic cystitis (HC) is a common side effect of cyclophosphamide therapy, which deserves new therapeutic strategies, such as those based on natural products. The ethanol extract of the inner bark of Caesalpinia pyramidalis (Tul.) (EECp) possesses anti-inflammatory, antinociceptive, and antioxidant activities as previously showed by our group. We have investigated the effect of EECp on the cyclophosphamide-induced HC. Cystitis was induced in male Wistar rats by the injection of cyclophosphamide. These animals were pretreated with EECp (100–400 mg/kg), vehicle, or mesna. Myeloperoxidase activity and malondialdehyde formation were measured in urinary bladder and other tissues. Bladder edema and histopathological alterations and serum nitric oxide metabolites concentration NOx- were also evaluated. Treatment with EECp (100–400 mg/kg) or mesna impaired the increase of myeloperoxidase activity in urinary bladder and the serum NOx- induced by cyclophosphamide but did not reduce edema in this tissue, as did mesna. Total histological score was reduced by EECp (100 mg/kg). Lung myeloperoxidase activity, which was increased by cyclophosphamide, was decreased significantly by EECp (400 mg/kg). EECp also diminished the malondialdehyde formation in bladder, lung, and spleen, although these parameters were not affected by cyclophosphamide. These results indicate that EECp reduced urinary bladder damage during cyclophosphamide-induced HC in rats.